Study guides

☆☆

Q: 4x2 plus 14x plus 12

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

6x2 + 14x -12 = (3x - 2) (2x + 6). There they are.

(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)

(2x+3)(2x+4)

4x2=12

4x2 - 16x + 12

Related questions

4x2 + 14x + 12 = 2(2x2 + 7x + 6) = 2(2x + 3)(x + 2)

4x2 plus 3=11

12

12

6x2 + 14x -12 = (3x - 2) (2x + 6). There they are.

If you mean: x^2 +14x +24 then it is (x+2)(x+12) when factored

(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)

(2x+3)(2x+4)

4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified

Do tou mean x2+14x+24? If so then it is (x+2)(x+12) when factored

4x2=12

x > 3

People also asked